The Influence of Guided Inquiry Learning Model on Students' Critical Thinking Skills in Thermodynamics Material - Ardian Sukandi; Joni Rokhmat; I Wayan Gunada (Postgraduate Program, University of Mataram, 2025)
This study aims to determine the effect of guided inquiry learning models on students' critical thinking skills in thermodynamics material. The type of research used is experimental research with a nonequivalent control group design. The population of this study was students of class XII MA Manba'ul Ulum in the 2024/2025 Academic Year. The research sample was taken using the cluster random sampling technique, so that 31 students of class XI MIA 1 were selected as the control class and 31 students of class XI MIA 2 as the experimental class. The experimental class was given treatment in the form of learning using the guided inquiry model, while the control class used the conventional model. Critical thinking ability data were obtained through the provision of a descriptive test of 10 questions and through a questionnaire given to students. The average value of critical thinking ability obtained during the pre-test of the two classes was the experimental class of 37.15 and the control class of 41.64. The average value after the implementation of the post-test increased in both classes, where the experimental class was 79.93 and the control class was 72.84. The critical thinking ability data of both classes were homogeneous and normally distributed. The critical thinking ability data were analyzed using the Independent Simple t test. The results of the SPSS data analysis obtained a t-count value of 3.199 with a significance level of 0.05% so that the t-table was 2.000, and the significant value obtained was 0.002, so the t-count> t-table or the significance value <significance level, then. Thus, it is concluded that there is an influence of the application of the guided inquiry learning model on students' critical thinking abilities in thermodynamics material.